Gestão metropolitana e o papel do município periférico: Itapecerica da Serra - Baldusco, Lacir Ferreira (2006)
Itapecerica da Serra is a county located 33 km from São Paulo within an enviromental protection area. Its origin dates back to the XVII century, during the jesuitic settlelment. Its urban characteristics were preserved until the second half of the XX century, when it was influenced by the process of metropolization, which was extended to most counties in Grande São Paulo. As a consequence, the county went through deep changes: the irregular occupation of the soil, the urban violence, the unemployment and the sudden growth of population, clear features of this process. Like many others, the county was not prepared to face these problems, so it became dependent of other government bodies for referring its problems. It is necessary to understand that the situation the county of Itapecerica is going through is not its own exclusivity, it is a historical consequence of the centralizing model established by the Portuguese state, when Brazil was settled. Understanding this model is learning about a primitive pattern of administration which, along the centuries, developed according to the interests and culture of the central governments to which they were subordinated. In Brazil, the Portuguese model that was implemented supported itself in the metropolis interests in settling and mainly expanding its wealth. This way, the Brazilian county is still an instrument working for the maintenance of power in a certain way. For this reason, it is possible to understand why this space, which is the only federate entity consisted of territory, people and government is not, has never been and will never be a complete federate entity in the short term, according to what has been established in the constitution of 1988. Therefore, the management instruments which have been created in the last years, such as the tax liability law and the city act, under the justification of establishing a new paradigm for the public administration, mainly for the county, are actually not instruments with enough power to change the reality of penury in which the counties, especially the ones located in the metropolitan areas, live. These are counties which shelter the most underpriviledged population of the country. They are satellites of the great metropolis, which relate to those in a constant movement of flow and counterflow, having no condition to react before the new demands.This way, the Brazilian county, weakest part of the federalism, depend on other entities for its political and administrative survival. It is dependent on financial transfers which concentrate mainly in the hands of the federal government and is also subject to political matters, once the prioritizing of public investments main criteria is based on the party, rather than on the real necessity of the county. Taking this model into consideration, we can get to a conclusion that the low urban quality of our cities results historically from this dependent descentralization process. As a solution, we get back to discuss the city as a democratic area of full public participation, in the patterns of Aristotle and Socrates s Greek polis, which take the participation of the population in the decisions on the city routes as the main management instrument in the city transformation. In order to get there, experiences such as the participative budget, the hydrographic Basin Committees and the Director Plan of Districts have appeared. These don t change the status quo of the federalism, taking advantage of the county autonomy conquered in the constitution of 1988 to creatively search ways for a more effective administration of our cities.